Cepharanthine: A Promising Old Drug against SARS‐CoV‐2. Issue 12 (1st July 2022) - Fan, Huahao; He, Shi‐ting; Han, Pengjun; Hong, Bixia; Liu, Ke; Li, Maochen; Wang, Shuqi; Tong, Yigang
Abstract: Recently, the inhibiting effects of a clinically approved drug Cepharanthine on severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) have attracted widespread attention and discussion. However, the public does not understand the relevant research progress very well. This paper aims to introduce a brief history of studies on the effects of cepharanthine against SARS‐CoV‐2, including "discovery of anti‐SARS‐CoV‐2 activity of cepharanthine in vitro", "potential mechanisms of cepharanthine against SARS‐CoV‐2", "confirmation of cepharanthine's anti‐SARS‐CoV‐2 activity in vivo", "potential approaches for improving the druggability of cepharanthine" and "clinical trials of cepharanthine treating SARS‐CoV‐2 infection". Taken together, cepharanthine is believed to be a promising old drug for coronavirus disease‐19 (COVID‐19) therapy. Abstract : Cepharanthine is a clinically approved drug mainly purified from the root tuber of plants including Stephania epigaea Lo, Stephania cepharantha Hayata, Stephania yunnanensis H.S.Lo, and so on. Moreover, it has recently been reported to possess a broad‐spectrum antiviral ability including, SARS‐CoV‐2 and related variants. Cepharanthine is believed to be a promising drug candidate for treating COVID‐19.